Spellman's standard handbook for wastewater operators - Spellman, Frank R. (CRC Press, 2011)
Retaining the same successful and proven format used in the bestselling first edition, Spellman's Standard Handbook for Wastewater Operators: Volume I, Fundamental Level, Second Edition contains the necessary information to successfully study for and pass currently administered certification examinations. Primarily designed to provide a readily accessible, user-friendly source of information for review in preparing for the first levels of licensure, this volume also sets the stage for Volumes II and III.